Review of the Sigmoid Function Implementation into Digital Hardware - Syahrulanuar, Ngah; Rohani, Abu Bakar; Abdullah, Embong (2015)
This paper discuss about the implementation of the sigmoid function into digital hardware. Several methods has been proposed such as lookup table (LUT), piecewise linear approximation (PWL), piecewise nonlinear approximation and CORDIC. Each method has their own advantages and disadvantages. Some researcher has start hybrid method by combining two or more the available methods for realizing the sigmoid function in digital hardware.